'Wicked problems' as catalysts for learning in educational ethics games. Issue 4 (2nd October 2021) - Nardo, Aline; Gaydos, Matthew
ABSTRACT: In this paper we discuss the potential of digital games to create meaningful educational experiences that contribute to the learning of ethics in higher education (HE) Science, Technology, Engineering and Mathematics (STEM) degrees. We describe the design of a new digital ethics game with a focus on the challenges we encountered when applying existing theoretical frameworks for educational games and propose ways to address these challenges. We contend that existing design frameworks fail to account for the 'wickedness' of ethical problems – i.e. their inconclusive, complex, and sometimes inherently contradictory nature – as they are centred around consequentiality and consistent game-system feedback to players' actions. Drawing from a Deweyan account of the 'educative experience' we seek to contribute to a domain-adequate theory of transformational experience and transformational play in the context of educational ethics game design.